Internationalization of family firms on innovation: Moderating impact of socioemotional wealth and institutional environment. - Lixin Zhou; Hanwei Zhou; Xiao Wei (PLoS ONE)
Currently, there is a lack of research specifically investigating the influence of internationalization on the innovation of family firms. This paper aims to investigate the influence of both internationalization depth and breadth on the innovation of family firms. Additionally, it aims to analyze how socioemotional wealth (SEW) and regional institutional environment in the home country influence this relationship. To test the hypotheses, a questionnaire survey was carried out with a sample of 253 family firms situated in eight provinces or municipalities in China. The results are as follows: First, internationalization depth negatively influenced family firm innovation, whereas internationalization breadth positively influenced family firm innovation. Second, the negative influence of internationalization depth on innovation was pronounced at a high level of family control, whereas the positive influence of internationalization breadth on innovation was pronounced at a low level of transgenerational succession intention in family firms. Third, a well-developed institutional environment strengthened the relationship between internationalization and innovation in family firms. This research enriches the literature on internationalization and innovation in family firms, and offers useful insights for practitioners.